A Comparison of the Accuracy of Four Age Estimation Methods Based on Panoramic Radiography of Developing Teeth - Shahrzad Javadinejad; Hajar Sekhavati; Roshanak Ghafari (Tabriz University of Medical Sciences, 2015)
Background and aims. Tooth development is widely used in determining age and state of maturity. Dental age is of high importance in forensic and pediatric dentistry and also orthodontic treatment planning .The aim of this study was to com-pare the accuracy of four radiographic age estimation methods. Materials and methods. Orthopantomographic images of 537 healthy children (age: 3.9-14.5 years old) were evaluated. Dental age of the subjects was determined through Demirjian's, Willem's, Cameriere's, and Smith's methods. Differences and correlations between chronological and dental ages were assessed by paired t-tests and Pearson's correlation analysis, respectively. Results. The mean chronological age of the subjects was 8.93 ± 2.04 years. Overestimations of age were observed follow-ing the use of Demirjian's method (0.87 ± 1.00 years), Willem's method (0.36 ± 0.87 years), and Smith's method (0.06 ± 0.63 years). However, Cameriere's method underestimated age by 0.19 ± 0.86 years. While paired t-tests revealed signifi-cant differences between the mean chronological age and ages determined by Demirjian's, Willem's, and Cameriere's methods (P < 0.001), such a significant difference was absent between chronological age and dental age based on Smith's method (P = 0.079). Pearson's correlation analysis suggested linear correlations between chronological age and dental age determined by all four methods. Conclusion. Our findings indicated Smith's method to have the highest accuracy among the four assessed methods. How-ever, all four methods can be used with acceptable accuracy.